An Electrochemical Study to Evaluate the Effect of Calcium Nitrite Inhibitor to Mitigate the Corrosion of Reinforcement in Sodium Chloride Contaminated Ca(OH)2 Solution. (23rd February 2017) - Ryu, Hwa-Sung; Singh, Jitendra Kumar; Lee, Han-Seung; Park, Won-Jun
Abstract : The effect of calcium nitrite (Ca(NO2 )2 ) was assessed by electrochemical means such as open circuit potential (OCP), electrochemical impedance spectroscopy (EIS), and potentiodynamic studies in saturated Ca(OH)2 solution contaminated with 0.99 and 7.91 g/L NaCl. The preliminary results of OCP showed that the potential is shifted towards positive (noble) side as content of inhibitor increased. The EIS results indicate that Ca(NO2 )2 works effectively in reduction and initiation of corrosion of steel rebar in NaCl contaminated Ca(OH)2 solution. Potentiodynamic studies revealed the pitting tendency of steel rebar exposed in 0.99 g/L NaCl at [Cl − /N O 2 - ] = 1.2 attributed to low conductivity of passive film which causes interference for Cl − ions attack during anodic polarization. The 85.75% efficiency is found in 0.99 g/L at [Cl − /N O 2 - ] = 1.2. The Ca(NO2 )2 inhibitor transformed the unstable iron oxides/hydroxides into stable and protective oxides/hydroxides due to its strong oxidizing nature. Therefore, this inhibitor is sufficiently and significantly reducing the corrosion of steel rebar at even its low concentration with 0.99 and 7.91 g/L NaCl solution.